Sum of our parts - Ang, Kimi (Nanyang Technological University, 2021)
This report aims to provide our audience with insights into Sum of Our Parts and its creation process. Our report will introduce in detail the context of the film, the stylistic choices in its presentation, and the motifs featured within the film - from the filmmaker’s perspective, as well as the artists’ perspectives. It also documents the process behind our documentary, from pre-production, to post-production, to the challenges that we faced.